Deconstructing the Authenticity Crisis: A Critical Analysis of Written Text Bias in Listening Evaluation in Elementary School - Rahmat Iqbal; Martines Martines; Intan Safiah; Rizki Kurniawati (Universitas Muhammadiyah Mataram, 2026)
Listening skills assessments in elementary school are often biased because written texts fail to represent the characteristics of authentic oral communication, as the listening tests given are only rigid written texts. This condition is further exacerbated because teachers believe that students' listening skills do not need to be optimally evaluated as they have been continuously developing since birth. This condition will result in biased evaluation of students' listening skills, which is far from the characteristics of authentic assessment, ultimately leading to poor listening skills. This research aims to deconstruct the conditions of listening evaluation thru a critical analysis of the assessment instruments used in elementary schools. Using a qualitative approach with content analysis methods, this study examines three assessment documents (test questions, listening transcripts, and rubrics) at SD Negeri 15 Banda Aceh. The research findings indicate a dominance of rigid scripted speech, high lexical density, and the absence of natural oral linguistic features such as redundancy and pauses in the evaluation instrument. This condition creates a bias where listening tests become